Method for preparing cementitious material from electrolytic manganese residue
Patent Information
- Application Number
- CN202611108811.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]基于上述技术问题,本发明目的是提供一种电解锰渣制备胶凝材料的方法,采用水渣、电解锰渣、赤泥复配水玻璃的配方,全程不添加水泥及熟料、不加热,用赤泥替代大部分工业碱,实现“以废制废”的创新,兼具降本与环保双重效果,胶凝材料成品力学性能和体积稳定性均能达到32.5水泥等级使用要求,解决40%以上高掺量下胶凝材料普遍强度低、膨胀开裂和性能不稳的问题,实现低碳绿色生产和电解锰渣的资源化再利用的目标
1.本发明引入电解锰渣作为硅铝骨科兼硫酸盐源,形成“赤泥(碱源)+锰渣(硫酸盐/硅铝源)+矿渣(活性硅铝)+水玻璃(补充碱/硅)”的四元协同体系,全程不添加水泥及熟料。四组分协同激发与反应平衡(碱度、硫酸盐、硅铝比、钙含量)使电解锰渣固废利用率提升至40%以上,所得胶凝材料3d抗压强度≥12MPa,28d抗压强度达33~39MPa,完全达到32.5水泥等级使用要求。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolytic manganese slag treatment technology, and specifically relates to a method for preparing cementitious materials from electrolytic manganese slag. Background Technology
[0002] Electrolytic manganese slag is an acidic waste residue produced during the electrolytic production of metallic manganese. Its main components are SiO2, Al2O3, and CaSO4·2H2O. It is characterized by high moisture content, high viscosity, and low activity, and is classified as Class II general industrial solid waste. Producing 1 ton of electrolytic metallic manganese generates 10-12 tons of electrolytic manganese slag. Cementitious materials are substances that, under physical and chemical action, can transform from a slurry into a solid, stone-like substance and can bind other materials to form a composite solid with a certain mechanical strength. Based on chemical composition, they are divided into inorganic cementitious materials (such as cement, lime, and gypsum) and organic cementitious materials (such as asphalt and resin).
[0003] The core defects of existing cementitious materials are: 1) Strength bottleneck: Strength drops sharply at high admixture levels. Admixture limitation: When manganese slag > 40%, the 3-day compressive strength is < 6.0 MPa, and the 28-day compressive strength is often < 25 MPa, lower than cement's 32.5 MPa, making it difficult to replace cement as a main material. Reasons: Manganese slag has many inert components and low activity; high gypsum content (15-30%) inhibits cement hydration, delays CSH formation, resulting in low early strength and slow later strength growth. 2) Poor volume stability: Sulfate expansion and cracking. Risk: SO4 in manganese slag. 2- 15-30% reacts with Al2O3 to form ettringite, which continues to expand in the later stages, leading to cracking, warping, and strength reduction in the hardened body. Higher dosages exacerbate the problem: SO4 2- Excessive AFt → disordered growth → increased porosity and loose structure. 3) Environmental risks: heavy metal leaching: containing Mn. 2+ Cr 6 + Pb 2+ As 3+ Mn leaching from the original residue 2+ The concentration can reach 0.46-0.97 mg / L, far exceeding the national standard; if solidification is incomplete, long-term leaching will pollute the soil / groundwater. 4) High pretreatment costs and energy consumption: High-temperature activation requires calcination at 600~800℃ for deammoniation and activation, resulting in high energy consumption, large equipment investment, and an increase in cost of 30~50 yuan / ton, making it uneconomical. Mechanical activation only improves fineness and cannot activate inert minerals, resulting in limited strength improvement and low cost-effectiveness. 5) Unclear hydration mechanism and difficult control: Multiphase complex system: Manganese slag-mineral slag-cement-gypsum coexist, the hydration reaction path is ambiguous, the formation of AFt and CSH is difficult to balance, and strength and stability are difficult to control in a coordinated manner. Large quality fluctuations: The composition of manganese slag fluctuates with the source of manganese ore and electrolysis process, resulting in poor batch stability, difficulty in precise production control, and high product quality dispersion.
[0004] Existing technologies mainly rely on "manganese slag + slag + cement + alkaline activator", with manganese slag content generally less than 40% and manganese slag utilization rate less than 10%, making it difficult to achieve large-scale, low-cost, and environmentally friendly utilization of manganese slag. Summary of the Invention
[0005] Based on the above-mentioned technical problems, the purpose of this invention is to provide a method for preparing cementitious materials from electrolytic manganese slag. This method employs a formula of water slag, electrolytic manganese slag, red mud, and water glass, without adding cement or clinker, and without heating. Red mud replaces most of the industrial alkali, achieving an innovative "waste-to-waste" approach. This method combines cost reduction and environmental protection, and the finished cementitious material meets the mechanical properties and volume stability requirements of 32.5 cement grade. It solves the problems of low strength, expansion cracking, and unstable performance commonly found in cementitious materials with high admixture content (above 40%), achieving the goals of low-carbon green production and the resource-based reuse of electrolytic manganese slag.
[0006] The specific technical solution is as follows: A method for preparing cementitious materials from electrolytic manganese slag includes the following steps: S1: Pre-treat the electrolytic manganese slag, water slag and red mud respectively to make their physicochemical properties meet the requirements for raw material use; S2: Mix electrolytic manganese slag, water slag, red mud and water glass in the following proportions by weight: 38-52 parts electrolytic manganese slag, 30-40 parts water slag, 13-15 parts red mud and 5-7 parts water glass. Grind the mixture to a specific surface area of 400±20 m² / kg to obtain a cementitious material.
[0007] In addition, the method for preparing cementitious materials from electrolytic manganese slag in the above-mentioned technical solution provided by the present invention may also have the following additional technical features: In the above technical solution, the composition of the electrolytic manganese slag by weight percentage is as follows: SiO2 19.32%, Al2O3 4.8%, Fe2O3 32.08%, CaO 4.36%, MgO 3.27%, ablation rate of 34.34%, particle size of 200~300 mesh, and moisture content ≤1%.
[0008] In the above technical solution, the composition of the water slag by weight percentage is as follows: SiO2 35.6%, Al2O3 11.95%, Fe2O3 0.24%, CaO 41.8%, MgO 7.82%, SO3 0.8%, ablation rate of 0.72%, specific surface area of 400±20 m² / kg, and water content ≤1%.
[0009] In the above technical solution, the composition of red mud by weight percentage is as follows: SiO2 18%, Al2O3 10%, Fe2O3 36%, CaO 20%, Na2O 6%, TiO2 2%, ablation rate 8%, and particle size 150~200 mesh.
[0010] In the above technical solution, the water glass is in powder form with a modulus of 2.4, and contains sodium oxide ≥7.0% by weight.
[0011] In the above technical solution, before use, the electrolytic manganese slag and red mud in step S1 are loosened by a bridge disperser in the raw material stockpile to eliminate lumps.
[0012] In the above technical solution, the mechanical properties of the cementitious material are: 3d compressive strength ≥12 MPa, and 28d compressive strength 33~39 MPa.
[0013] The method for preparing cementitious materials from electrolytic manganese slag of the present invention has the following advantages compared with the prior art: 1. This invention introduces electrolytic manganese slag as a silica-alumina aggregate and sulfate source, forming a quaternary synergistic system of "red mud (alkali source) + manganese slag (sulfate / silica-alumina source) + slag (active silica-alumina) + water glass (supplementary alkali / silicon)," without adding cement or clinker throughout the process. The synergistic activation and reaction balance of the four components (alkalinity, sulfate, silica-alumina ratio, calcium content) increases the utilization rate of electrolytic manganese slag solid waste to over 40%. The resulting cementitious material has a 3-day compressive strength ≥12MPa and a 28-day compressive strength of 33~39MPa, fully meeting the requirements for use with 32.5 cement grade.
[0014] 2. Red mud can replace sodium hydroxide and carbide slag as a natural alkaline activator, simultaneously fulfilling the quadruple roles of "alkali source + solidifying agent + cost reduction carrier + solid waste disposal". The alkaline components in red mud can effectively activate water slag and manganese slag, promoting synergistic effects among solid waste components. This avoids the corrosion and environmental risks of strong alkalis, reduces raw material costs, and is suitable for large-scale industrial production.
[0015] 3. This invention breaks with the traditional understanding that "sulfates in manganese slag inevitably lead to expansion and damage." Sulfates in manganese slag are stabilized in a red mud-water glass system. By controlling the alkalinity and the sulfate-to-aluminum ratio, AFt is generated in an orderly manner and forms a dense gel-needle interpenetrating framework structure with CSH gel. The resulting cementitious material exhibits a 28-day shrinkage rate ≤0.02%, with no subsequent expansion or cracking, and passes both volume stability tests (patches and Le Chatelier test).
[0016] 4. The leaching concentrations of Cr, As, and Pb in the cementitious material of this invention are all far below the limits specified in the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification," and the leaching concentration of Mn is far below the Class V water quality standard limit specified in the "Environmental Quality Standard for Surface Water." Heavy metals are stably solidified through multiple mechanisms, including precipitation, encapsulation, and lattice substitution, ensuring complete compliance with environmental safety standards.
[0017] 5. This invention requires no high-temperature calcination or the addition of cement clinker throughout the entire process, and can be completed at room temperature, reducing carbon emissions from the source. The process is simple, with low raw material costs and stable batch performance, enabling large-scale synergistic resource utilization of two major industrial solid wastes: electrolytic manganese slag and red mud. Attached Figure Description
[0018] Figure 1 This is a flowchart of a method for preparing cementitious materials from electrolytic manganese slag according to the present invention; Figure 2 This is a schematic diagram of the structure of an embodiment of the bridge disperser of the present invention; Figure 3 for Figure 1 The left view; in, Figures 2 to 3 The correspondence between the reference numerals and component names in the attached drawings is as follows: 1. Concrete base, 2. Lower slide rail, 3. Upper crossbeam, 4. Upper slide rail, 5. Disintegration wheel. Detailed Implementation
[0019] The following are specific implementation cases and appendices. Figure 1-3 The present invention will be further described, but the present invention is not limited to these embodiments.
[0020] A method for preparing cementitious materials from electrolytic manganese slag includes the following steps: S1: Pre-treat the electrolytic manganese slag, water slag and red mud respectively to make their physicochemical properties meet the requirements for raw material use; S2: Mix electrolytic manganese slag, water slag, red mud and water glass in the following proportions by weight: 38-52 parts electrolytic manganese slag, 30-40 parts water slag, 13-15 parts red mud and 5-7 parts water glass. Grind the mixture to a specific surface area of 400±20 m² / kg to obtain a cementitious material.
[0021] The role of electrolytic manganese slag is as a main aggregate and silicon-aluminum raw material, containing sulfates, and is used for high-volume disposal of bulk solid waste. The role of water slag is as a highly active silicon-aluminum glass, which, after alkali activation, generates C-S-H (hydrated calcium silicate) and C-A-H (hydrated calcium aluminate), providing the main mechanical strength. The role of red mud is to replace sodium hydroxide and carbide slag, acting as a natural alkaline activator to activate the water slag and manganese slag, resulting in synergistic effects among the solid waste components, reducing costs and carbon emissions. The role of water glass is to supplement alkalinity and provide an active silicon source, enhancing the alkali activation reaction, densifying the microstructure, and inhibiting expansion.
[0022] In an embodiment of the present invention, the composition of the electrolytic manganese slag by weight percentage is as follows: SiO2 19.32%, Al2O3 4.8%, Fe2O3 32.08%, CaO 4.36%, MgO 3.27%, ablation rate of 34.34%, particle size of 200~300 mesh, and moisture content ≤1%.
[0023] In an embodiment of the present invention, the water slag is composed of the following components by weight percentage: SiO2 35.6%, Al2O3 11.95%, Fe2O3 0.24%, CaO 41.8%, MgO 7.82%, SO3 0.8%, ablation rate of 0.72%, specific surface area of 400±20 m² / kg, and water content ≤1%.
[0024] In an embodiment of the present invention, the red mud is composed of the following components by weight percentage: SiO2 18%, Al2O3 10%, Fe2O3 36%, CaO 20%, Na2O 6%, TiO2 2%, ablation rate of 8%, and particle size of 150-200 mesh.
[0025] In an embodiment of the present invention, the water glass is in powder form with a modulus of 2.4, wherein sodium oxide contains ≥7.0% by weight.
[0026] In an embodiment of the present invention, before use, the electrolytic manganese slag and red mud in step S1 are loosened by a bridge disperser in the raw material stockpile to eliminate lumps.
[0027] In an embodiment of the present invention, the mechanical properties of the cementitious material are: 3d compressive strength ≥12 MPa, and 28d compressive strength 33~39 MPa.
[0028] Example 1: The composition of electrolytic manganese slag, by weight percentage, is: SiO2 19.32%, Al2O3 4.8%, Fe2O3 32.08%, CaO 4.36%, MgO 3.27%, with an ablation rate of 34.34%, particle size of 200-300 mesh, and moisture content ≤1%. Source: Laibin Manganese Industry. The composition of water slag, by weight percentage, is: SiO2 35.6%, Al2O3 11.95%, Fe2O3 0.24%, CaO 41.8%, MgO 7.82%, SO3 0.8%, with an ablation rate of 0.72%, particle size: specific surface area 400±20 m² / g, and moisture content ≤1%. Source: Liuzhou Steel Plant. The composition of the red mud, by weight percentage, is: SiO2 18%, Al2O3 10%, Fe2O3 36%, CaO 20%, Na2O 6%, TiO2 2%, with an ablation rate of 8% and a particle size of 150-200 mesh. The water glass is in powder form, with a modulus of 2.4, and by weight percentage, contains ≥7.0% sodium oxide. It is yellowish-green in appearance and is of industrial grade.
[0029] Before use, electrolytic manganese slag and red mud are loosened in the raw material stockpile using a bridge-type disperser to eliminate lumps. See Figure 1-2 The bridge-type disperser structure used in this embodiment of the invention includes a concrete base 1, a lower slide rail 2, an upper crossbeam 3, an upper slide rail 4, and a dispersing wheel 5. The dispersing wheel 5 is driven to rotate by a motor. The mounting frame of the dispersing wheel 5 moves left and right on the upper slide rail 4. The concrete base 1 is supported at the bottom of the lower slide rail. The upper crossbeam 3 moves back and forth along the lower slide rail 2 to disperse the raw materials within the covered stockpile area, so that the raw materials maintain uniform particle size and looseness, which facilitates subsequent uniform mixing.
[0030] The specific preparation steps of the method for preparing cementitious materials from electrolytic manganese slag according to an embodiment of the present invention are as follows: raw material pretreatment, the electrolytic manganese slag and red mud are expanded to make their physicochemical properties meet the requirements for raw material use; mixing and grinding, the electrolytic manganese slag, water slag, red mud and water glass are mixed in proportion by weight, and the mixture is ground to a specific surface area of 400±20m² / g, which is also a necessary process for physical activation and chemical activation, to obtain cementitious materials.
[0031] Design Examples 1-3 and Comparative Examples 1-3 to obtain gel materials, the ingredient list of which is shown in Table 1, in grams.
[0032] The mechanical properties of this invention were tested in accordance with GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)"; the leaching test was performed in accordance with HJ 557-2010 "Leaching Toxicity of Solid Waste - Horizontal Oscillation Method" and GB5085.3-2007, GB3838-2002V: the solidified body cured for 28 days was crushed to a particle size ≤3mm, deionized water was added at a liquid-to-solid ratio of 10:1, and the mixture was horizontally oscillated at 25℃ for 240min. After filtration, the concentration of heavy metal ions in the filtrate was measured.
[0033]
[0034] Cementitious material samples were prepared from the cementitious materials obtained in Examples 1-3 and Comparative Examples 1-3. The standard for preparing the cementitious material samples was GB / T17671.
[0035] Take 450 grams of cementitious material, add 1350 grams of standard sand and 225 grams of water, stir evenly, vibrate to form a mold, and place the sample under standard curing conditions, i.e., a constant temperature and humidity chamber at 20±2℃, to allow it to solidify and harden, finally obtaining a cementitious material sample block.
[0036] Mechanical property tests were conducted on cementitious material samples according to their age. The compressive strength was tested according to standard GB175-2023, the density according to standard GB / T208-2014, the volumetric stability according to standard GB175-2023, and the quality uniformity according to standard GB175-2023 (measurement of coefficient of variation). The steps are as follows: (1) The performance of cementitious material samples was tested in accordance with relevant standards. The strength was tested by a cement compressive strength tester and the volume stability was tested by autoclaving. The volume stability test cake and the Le Chatelier test were qualified. (2) Results analysis: The experimental data were organized and analyzed to draw conclusions. The mechanical properties of the cementitious material samples obtained in Example 1-3 and Comparative Example 1-3 are shown in Table 2.
[0037]
[0038] Heavy metal leaching tests were conducted on the cementitious materials in Examples 1-3 and Comparative Examples 1-3, according to the standards GB5085.3-2007 and GB3838-2002V. The cementitious material of this invention has a 28-day drying shrinkage rate of ≤0.02%, exhibiting low shrinkage and good volume stability. It can effectively reduce the risk of cracking and deformation during the hardening process, improve the dimensional accuracy and durability of the structure, and is suitable for the construction of large-volume and thin-walled components.
[0039] The softening coefficient of the cementitious material of this invention is ≥0.92, indicating that the material can maintain high strength and good water resistance in long-term immersion or humid environments. It can be used in underground, hydraulic and high-humidity environment engineering, significantly improving the service stability of the material in aquatic environments.
[0040] Data from the heavy metal leaching experiment are shown in Table 3; data on the heavy metal leaching concentrations are shown in Table 4.
[0041]
[0042]
[0043] Analysis of heavy metal solidification effect: The leaching concentrations of Cr, As, and Pb in each case were far below the limits of the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification", and the leaching concentration of Mn was also far below the limit of Class V water quality standard of the "Surface Water Environmental Quality Standard", and the environmental safety fully met the standards.
[0044] The shortcomings of the comparative system are as follows: Comparative Example 1 has no water slag synergy, and due to the single active component, the hydration products are loose, with poor mechanical properties and a significantly higher amount of heavy metal leaching; Comparative Example 2 has no alkali activator, so the system has insufficient hydration activity and weak gelation ability; Comparative Example 3 is a cement substitute system, which not only has a low solid waste resource utilization rate, but also has a significantly inferior heavy metal sealing and solidification effect compared to the compounding scheme of this invention.
[0045] In this invention, the sulfate in the electrolytic manganese slag itself forms an intrinsic self-activating effect, which is combined with red mud to replace part of the traditional alkaline raw materials, and supplemented with an appropriate amount of water glass for further activation. The sulfate in the manganese slag, together with water glass and red mud, forms a multi-element synergistic activation system, which fully activates the activity of the cementing components and reduces the amount of strong alkali added. This not only realizes the resource utilization of manganese slag and red mud, two major industrial solid wastes, and reduces production costs, but also weakens the problems of efflorescence and corrosion caused by strong alkali alone, resulting in a dense structure and stable and reliable overall performance of the hardened body.
[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing cementitious materials from electrolytic manganese slag, characterized in that, Includes the following steps: S1: Pre-treat the electrolytic manganese slag, water slag and red mud respectively to make their physicochemical properties meet the requirements for raw material use; S2: Mix electrolytic manganese slag, water slag, red mud and water glass in the following proportions by weight: 38-52 parts electrolytic manganese slag, 30-40 parts water slag, 13-15 parts red mud and 5-7 parts water glass. Grind the mixture to a specific surface area of 400±20 m² / kg to obtain a cementitious material.
2. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, The composition of the electrolytic manganese slag by weight percentage is as follows: SiO2 19.32%, Al2O3 4.8%, Fe2O3 32.08%, CaO 4.36%, MgO 3.27%, ablation rate of 34.34%, particle size of 200~300 mesh, and moisture content ≤1%.
3. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, The composition of the water slag by weight percentage is as follows: SiO2 35.6%, Al2O3 11.95%, Fe2O3 0.24%, CaO 41.8%, MgO 7.82%, SO3 0.8%, ablation rate of 0.72%, specific surface area of 400±20 m² / kg, and water content ≤1%.
4. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, The red mud is composed of the following components by weight percentage: SiO2 18%, Al2O3 10%, Fe2O3 36%, CaO 20%, Na2O 6%, TiO2 2%, with an ablation rate of 8% and a particle size of 150~200 mesh.
5. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, The water glass is in powder form with a modulus of 2.4, and contains ≥7.0% sodium oxide by weight percentage.
6. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, In step S1, before use, the electrolytic manganese slag and red mud are loosened in the raw material stockpile using a bridge disperser to eliminate lumps.
7. The method for preparing cementitious materials from electrolytic manganese slag according to claim 1, characterized in that, The mechanical properties of the cementitious material are: 3d compressive strength ≥12 MPa, and 28d compressive strength 33~39 MPa.